A conceptual model for e-commerce adoption in developing countries: a task-technology fit perspective. (11th June 2007) - Vatanasakdakul, Savanid; D'Ambra, John
The adoption of B2B e-commerce in developed economies has, overall, been successful. This success, however, has not been reflected in developing countries, indicating that models for IT adoption in developed economies may not be appropriate. In response to this we develop a strategic fit perspective to investigate the issue of successful adoption of interorganisational information technologies in developing countries. This perspective is operationalised through the Task-Technology Fit (TTF) model by integrating interorganisational theories and theories of national culture. The model demonstrates that in an interorganisational context the fit of technologies to support tasks may not have the desired impact on performance in developing economies without considering the precursors of utilisation, national culture, the nature of business relationships, and the readiness of the technological infrastructure in the implementation environment. The model may be useful for better understanding how organisations in developing countries may adopt e-commerce technologies enabling online business processes in B2B settings.